Lithium Storage in Carbon Cloth–Supported KNb3O8 Nanorods Toward a High‐Performance Lithium‐Ion Capacitor. Issue 8 (13th August 2021) - Sun, Hui; Niu, Fei; Yuan, Peng; He, Xuexia; Sun, Jie; Liu, Zonghuai; Li, Qi; Lei, Zhibin
Abstract : Lithium‐Ion Capacitor In article number 2100029, Hui Sun, Qi Li, Zhibin Lei, and co‐workers report the successful growth of KNb3 O8 nanorods on the conductive carbon cloth (CC) towards high‐energy and long‐life lithium‐ion capacitor. The short KNb3 O8 nanorods, the enhanced conductivity and the negligible volume expansion during continuous charging/discharging process make the KNb3 O8 one of promising niobium‐based anodes towards future high‐energy charge storage device.